Caldera Life-Cycles of the Yellowstone Hotspot Track: Death and Rebirth of the Heise Caldera. (25th July 2018) - Jean, Marlon M; Christiansen, Eric H; Champion, Duane E; Vetter, Scott K; Phillips, William M; Schuth, Stephan; Shervais, John W
Abstract: As one of the most geochemically unique drill cores recovered within the Yellowstone–Snake River Plain (YSRP) province, the Sugar City geothermal test well was drilled into intra-caldera rhyolite lavas and tuffs erupted during the middle to late Pliocene and the resurgent basaltic volcanism erupted during the Pleistocene. This sequence parallels the two main stages proposed for YSRP hotspot calderas: i.e. the eruption of several large-volume, ash-flow tuff sheets followed by caldera collapse, then cessation of major rhyolitic activity and gradual subsidence accompanied by filling and eventual burial of the caldera by basalt lava flows. We employ stratigraphic relationships, paleomagnetism, and major, trace element, and Sr–Nd isotope geochemistry to develop models for the origin of the basaltic and rhyolitic magmas within a geographical and temporal context. The basalts are characterized by distinct groupings based on depth and geochemistry and reflect the dominant compositions observed on the surface, e.g. Snake River olivine tholeiite (SROT) and evolved type (e.g. Craters of the Moon). We also observe contaminated basalts that interacted with rhyolite/granite. The basaltic magma formed by shallow partial melting in the plume channel carved into the lithosphere. The older rhyolites preserve the classical characteristics of A-type granites and display major element and trace element concentrations typical for Eastern SRP caldera centres and minimal stratigraphic variation. Multiple lines of evidence document extensive magmatic differentiation and coupled basalt–rhyolite interactions. We find that the most plausible origin for the rhyolites is via partial melting of a hybrid source, comprising Archean crustal components and younger juvenile mafic intrusions. Assimilation of hydrothermally altered material is also required for some eruptive units. The rhyolites did not evolve from residual magma left over from the climactic Kilgore eruption (4·0 Ma), but instead represent discrete magma generation events in the course of a few hundred thousand years between 4·0 to 3·8 Ma. Beginning at approximately 3.3 Ma, basalts were able to erupt through the solidified composite pluton that formed below the caldera. The transition from rhyolite to basalt is tied to the declining flux of basaltic magma as North America moved away from the Yellowstone hotspot core.